Ultrahigh molecular weight polyethylene fiber as well as preparation method and application thereof

By adding antioxidants and fillers to ultra-high molecular weight polyethylene fibers, the problems of corrosion resistance and low strength of traditional adsorbent materials are solved, and fibers with high adsorption capacity and excellent mechanical properties are prepared, which are suitable for wastewater treatment.

CN119900100AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311409766.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

Adsorbent materials used in traditional wastewater treatment are not corrosion-resistant and have low strength, limiting their application range.

Method used

Ultra-high molecular weight polyethylene fiber is used to improve the corrosion resistance and adsorption properties of the fiber by adding antioxidants and fillers.

Benefits of technology

The prepared ultra-high molecular weight polyethylene fibers have high adsorption capacity (200-600mg/g), high strength and high modulus, and are suitable for wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of fiber preparation, and discloses an ultra-high molecular weight polyethylene fiber with an adsorption effect as well as a preparation method and application thereof, the ultra-high molecular weight polyethylene fiber is prepared from the following raw materials: ultra-high molecular weight polyethylene powder, an antioxidant and a filler; wherein the antioxidant accounts for 0.2 wt%-1 wt% of the ultra-high molecular weight polyethylene powder, and the filler accounts for 0.5 wt%-3 wt% of the ultra-high molecular weight polyethylene powder; wherein the filler is obtained by dissolving a metal salt and a polyacid organic ligand in a first solvent for reaction, by adopting the technical scheme provided by the invention, the ultra-high molecular weight polyethylene powder has good corrosion resistance, the adsorption performance of the ultra-high molecular weight polyethylene is improved through the filler, and the service life of the ultra-high molecular weight polyethylene powder is prolonged. The prepared ultra-high molecular weight polyethylene fiber with the adsorption effect is high in specific strength and high in specific modulus, and the adsorption capacity of the ultra-high molecular weight polyethylene fiber is as high as 200-600 mg / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fiber preparation, and in particular to an ultra-high molecular weight polyethylene fiber with adsorption function and a preparation method and application thereof. Background Art

[0002] Wastewater purification by adsorption is a new method of sewage treatment. However, traditional related carriers, such as polyester, acrylic, etc., are not corrosion-resistant, have low strength, and are easily damaged during use, which to a certain extent limits the use of this method. Therefore, it is necessary to develop corrosion-resistant and adsorbent materials.

[0003] Ultra-high molecular weight polyethylene fiber has excellent mechanical properties such as light weight, corrosion resistance, high specific strength, high specific modulus, and stable chemical properties. It has attracted attention from various countries and is widely used in aerospace, military bulletproof equipment, aquaculture, sporting goods and other fields. At present, there is no research on the application of ultra-high molecular weight polyethylene fiber in sewage treatment. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of the conventional adsorption materials in the prior art that they are not resistant to corrosion and have low strength, and to provide an ultra-high molecular weight polyethylene fiber with adsorption function and a preparation method and application thereof. The ultra-high molecular weight polyethylene fiber prepared by the method has good adsorption capacity, and due to the addition of the ultra-high molecular weight polyethylene fiber, the material also has good corrosion resistance.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides an ultra-high molecular weight polyethylene fiber, which includes ultra-high molecular weight polyethylene powder, an antioxidant and a filler, wherein the antioxidant accounts for 0.2-1wt% of the ultra-high molecular weight polyethylene powder, and the filler accounts for 0.5-3wt% of the ultra-high molecular weight polyethylene powder; wherein the filler is obtained by dissolving a metal salt and a polyacid organic ligand in a first solvent and reacting them.

[0006] The second aspect of the present invention provides a method for preparing ultra-high molecular weight polyethylene fibers, wherein a spinning solution containing a second solvent, ultra-high molecular weight polyethylene powder, an antioxidant, and a filler is spun to obtain the ultra-high molecular weight polyethylene fibers.

[0007] A third aspect of the present invention provides an application of ultra-high molecular weight polyethylene fiber in sewage treatment.

[0008] By adopting the technical scheme provided by the present invention, the ultra-high molecular weight polyethylene powder has good corrosion resistance, and the adsorption performance of the ultra-high molecular weight polyethylene is improved by fillers to prepare ultra-high molecular weight polyethylene fibers with adsorption effect, which have high specific strength and high specific modulus, and the adsorption capacity is as high as 200-600 mg / g. DETAILED DESCRIPTION

[0009] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0010] The first aspect of the present invention provides an ultra-high molecular weight polyethylene fiber, wherein the raw materials for preparing the ultra-high molecular weight polyethylene fiber include ultra-high molecular weight polyethylene powder, an antioxidant and a filler; wherein the antioxidant accounts for 0.2-1wt% of the ultra-high molecular weight polyethylene powder, and the filler accounts for 0.5-3wt% of the ultra-high molecular weight polyethylene powder; wherein the filler is obtained by dissolving a metal salt and a polyacid organic ligand in a first solvent and reacting them.

[0011] The content of ultra-high molecular weight polyethylene powder directly affects the strength and modulus of the product, and the content of filler directly affects the adsorption capacity of the product. Based on the total amount of the ultra-high molecular weight polyethylene powder, the antioxidant can account for any value within the numerical range of any two of 0.2%, 0.5%, 0.8%, and 1% of the ultra-high molecular weight polyethylene powder, and the filler can account for any value within the numerical range of any two of 0.5%, 1%, 1.5%, 2%, 2.5%, and 3% of the ultra-high molecular weight polyethylene powder. In some embodiments of the present invention, an ultra-high molecular weight polyethylene powder with a weight average molecular weight of 4 million to 4.5 million g / mol is selected.

[0012] In some embodiments of the present invention, preferably, based on the total amount of the ultra-high molecular weight polyethylene powder, the antioxidant accounts for 0.6-0.8wt% of the ultra-high molecular weight polyethylene powder, and the filler accounts for 2-3wt% of the ultra-high molecular weight polyethylene. The antioxidant can account for any value within the numerical range of any two of 0.6%, 0.7%, and 0.8% of the ultra-high molecular weight polyethylene powder, and the antioxidant can account for any value within the numerical range of any two of 2%, 2.2%, 2.5%, 2.8%, and 3% of the ultra-high molecular weight polyethylene.

[0013] In some embodiments of the present invention, preferably, the ultra-high molecular weight polyethylene fiber has an adsorption capacity of 200-600 mg / g, a strength of 25-40 cN / dtex, a modulus of 1300-1600 cN / dtex, and a melting temperature of 140-150° C. The adsorption capacity refers to the mass of the dye solution adsorbed by the ultra-high molecular weight polyethylene fiber per unit mass at 30° C. for 10 hours, and the dye solution used is generally methylene blue. The adsorption capacity of the ultra-high molecular weight polyethylene fiber can be any value within the range of values ​​formed by any two of 200 mg / g, 300 mg / g, 400 mg / g, 500 mg / g, and 600 mg / g, the strength can be any value within the range formed by any two of 25 cN / dtex, 30 cN / dtex, 35 cN / dtex, and 40 cN / dtex, and the modulus can be any value within the range formed by any two of 1300 cN / dtex, 1400 cN / dtex, 1500 cN / dtex, and 1600 cN / dtex. The strength and modulus are measured according to GB / T 14344-2008, and the melting temperature is measured according to GB / T 19466.3-2004.

[0014] In the present invention, the filler is obtained by dissolving a metal salt and a polyacid organic ligand in a first solvent and reacting them, which can specifically include dissolving 1-5 parts by weight of polyvinyl pyrrolidone in 100 mL of the first solvent, heating and stirring, then adding the metal salt and the polyacid, continuing the reaction at 110-130° C. for 0.5-3 hours, and then centrifuging and washing to obtain the filler.

[0015] In some embodiments of the present invention, preferably, the first solvent is a mixed solution of ethanol and N,N-dimethylformamide, wherein the volume ratio of ethanol to N,N-dimethylformamide is 3:7-7:3.

[0016] In some embodiments of the present invention, preferably, the metal salt is selected from at least one of zinc salt, copper salt, cobalt salt and nickel salt. The selected metal salt needs to be easily soluble in the first solvent.

[0017] In other embodiments of the present invention, preferably, the zinc salt is selected from at least one of zinc nitrate, zinc acetate, and zinc chloride, the copper salt is selected from at least one of copper nitrate, copper acetate, and copper chloride, the cobalt salt is selected from at least one of cobalt nitrate, cobalt acetate, and cobalt chloride, and the nickel salt is selected from at least one of nickel nitrate, nickel acetate, and cobalt chloride.

[0018] In some embodiments of the present invention, preferably, the polyacid organic ligand is selected from at least one of terephthalic acid, 1,4-naphthalene dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, 2,2'-biphenyl dicarboxylic acid, 2,5-dihydroxy terephthalic acid, and 3,3',5,5'-biphenyl tetracarboxylic acid. When preparing the filler, the selected metal salt and organic ligand will directly affect the adsorption performance of the product, especially the filler prepared from terephthalic acid, 1,4-naphthalene dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid and the selected metal salt has better adsorption performance.

[0019] In some embodiments of the present invention, preferably, the metal salt is 0.1-0.5 parts by weight, and the polyacid organic ligand is 0.05-0.3 parts by weight. Generally speaking, in the case of the same type, the more parts of the metal salt, the stronger the absorption capacity of the obtained filler, the parts of the metal salt can be any value within the range formed by any two of 0.1, 0.2, 0.3, 0.4, and 0.5, and the parts of the polyacid organic ligand can be any value within the range formed by any two of 0.05, 0.1, 0.15, 0.2, 0.25, and 0.3.

[0020] In some embodiments of the present invention, preferably, the metal salt is 0.2-0.4 parts by weight, and the polyacid organic ligand is 0.1-0.2 parts by weight. The weight of the metal salt can be any value within the range formed by any two of 0.2, 0.3, and 0.4, and the weight of the polyacid organic ligand can be any value within the range formed by any two of 0.1, 0.12, 0.15, 0.18, and 0.2.

[0021] In other embodiments of the present invention, the antioxidant is selected from one or more of tris(4-nonylphenyl)phosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl, and vitamin E. The selected antioxidant does not develop color or volatilize during processing, can remain stable, and is easily dispersed in the spinning solution.

[0022] In some embodiments of the present invention, preferably, a dispersant is also dissolved in the first solvent, and the dispersant plays a stabilizing role in maintaining the product particles. The dispersant is polyvinyl pyrrolidone, and the content is 1-5 parts, and specifically can be any value within the range formed by any two of 1, 3, and 5.

[0023] The second aspect of the present invention provides a method for preparing ultra-high molecular weight polyethylene fiber, wherein a spinning solution containing a second solvent, ultra-high molecular weight polyethylene powder, an antioxidant, and a filler is spun to obtain the ultra-high molecular weight polyethylene fiber; wherein the filler is obtained by dissolving a metal salt and a polyacid organic ligand in a first solvent and reacting them.

[0024] In some embodiments of the present invention, preferably, the ultra-high molecular weight polyethylene powder accounts for 5-10 wt % of the second solvent.

[0025] In some embodiments of the present invention, preferably, the antioxidant accounts for 0.2-1 wt% of the ultra-high molecular weight polyethylene powder, and the filler accounts for 0.5-3 wt% of the ultra-high molecular weight polyethylene powder.

[0026] The proportion of ultra-high molecular weight polyethylene affects the molecular weight of the obtained product. The greater the concentration of ultra-high molecular weight polyethylene, the greater the shearing effect on the unit volume of polyethylene, and the greater the thermal degradation effect, which leads to a decrease in the molecular weight of the fiber. The content of the filler will affect the adsorption performance of the product, so it is necessary to set a suitable ratio. The ultra-high molecular weight polyethylene powder can account for any value within the range formed by any two values ​​of 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, and 10wt% of the second solvent.

[0027] In some embodiments of the present invention, preferably, the process of forming the spinning solution includes: dispersing the ultra-high molecular weight polyethylene powder, antioxidant, and filler in the second solvent to form the spinning solution. The second solvent can dissolve the corresponding raw materials, and specifically can be decalin.

[0028] In some embodiments of the present invention, preferably, the dispersion process comprises: ultrasonic-assisted stirring at 50-100° C. for 1-4 h.

[0029] In some other embodiments of the present invention, preferably, the dispersion process includes: ultrasonic-assisted stirring at 70-90° C. for 2-3 h.

[0030] The dispersion time and temperature affect the strength and modulus of the prepared product. The dispersion time can be any value within the range formed by any two values ​​of 1h, 2h, 3h, and 4h, or any value within the range formed by any two values ​​of 2h, 2.2h, 2.5h, 2.8h, and 3h. The dispersion temperature can be any value within the range formed by any two values ​​of 50°C, 60°C, 70°C, 80°C, 90°C, and 100°C, or any value within the range formed by any two values ​​of 70°C, 75°C, 80°C, 85°C, and 90°C.

[0031] Ultrasonic assistance is used during dispersion to facilitate more uniform and faster dispersion of the mixture. The ultrasonic power is 300-1000w, preferably 500-800w. The ultrasonic power can be any value within the range formed by any two values ​​of 300w, 500w, 600w, 700w, 800w, and 1000w.

[0032] In some embodiments of the present invention, preferably, the spinning process comprises: stretching, wherein the stretching ratio is 25-50 times.

[0033] In some other embodiments of the present invention, preferably, the drafting ratio is 30-40 times.

[0034] The stretching ratio also has a great influence on the modulus, strength, etc. of the product. The stretching ratio can be any value within the range formed by any two values ​​of 25 times, 30 times, 35 times, 40 times, 45 times, and 50 times, or any value within the range formed by any two values ​​of 30 times, 32 times, 35 times, 38 times, and 40 times; the stretching temperature can be any value within the range formed by any two values ​​of 130°C, 135°C, 140°C, 145°C, 150°C, and 155°C, or any value within the range formed by any two values ​​of 135°C, 138°C, 140°C, 142°C, and 145°C.

[0035] In some implementation methods of the present invention, the spinning process further includes adding the spinning solution to a twin-screw extruder before stretching, extruding through a spinneret to form primary filaments, and then stretching the primary filaments.

[0036] In some embodiments of the present invention, preferably, the working pressure of the twin-screw extruder is 2.0-5.0 MPa, and its working process includes feeding, homogenization and conveying, wherein the temperature of the feeding section is 70-150°C, the temperature of the homogenization section is 120-170°C, and the temperature of the conveying section is 130-180°C.

[0037] In some other embodiments of the present invention, preferably, the working pressure of the twin-screw extruder is 3-4 MPa, the temperature of the feeding section is 90-140°C, the temperature of the homogenizing section is 150-160°C, and the temperature of the conveying section is 150-170°C.

[0038] In some embodiments of the present invention, preferably, the spinning temperature is 150-180° C., and the spinning pressure is 2-5 MPa.

[0039] In some other embodiments of the present invention, preferably, the spinning temperature is 160°C-170°C, and the spinning pressure is 3-4 MPa.

[0040] The working pressure of the twin-screw extruder can be any value within the range formed by any two values ​​of 2MPa, 3MPa, 4MPa, and 5MPa, and can also be any value within the range formed by any two values ​​of 3.0MPa, 3.2MPa, 3.5MPa, 3.8MPa, and 4.0MPa; the temperature of the feeding section can be any value within the range formed by any two values ​​of 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C; the temperature of the homogenizing section can be any value within the range formed by any two values ​​of 120°C, 130°C, 140°C, 150°C, and 160°C, and can also be any value within the range formed by any two values ​​of 150°C, 152°C, 155°C, 158°C, and 160°C; the temperature of the conveying section can be 130°C, 140°C, 150°C, 160°C , 170°C, and 180°C, and can also be any numerical value within the range formed by any two numerical values ​​of 150°C, 155°C, 160°C, 165°C, 170°C, and 180°C; the spinning temperature is any numerical value within the range formed by any two numerical values ​​of 150°C, 160°C, 170°C, and 180°C, and can also be any numerical value within the range formed by any two numerical values ​​of 160°C, 160°C, 162°C, 165°C, 168°C, and 170°C; the spinning pressure can be any numerical value within the range formed by any two numerical values ​​of 2.0MPa, 3.0MPa, 4.0MPa, and 5.0MPa, and can also be any numerical value within the range formed by any two numerical values ​​of 3.0MPa, 3.2MPa, 3.5MPa, 3.8MPa, and 4.0MPa.

[0041] A third aspect of the present invention provides an application of ultra-high molecular weight polyethylene fiber in sewage treatment.

[0042] The ultra-high molecular weight polyethylene fiber obtained by the invention has strong adsorption capacity and good mechanical strength. Since the polyethylene material is acid-resistant, alkali-resistant and solvent-resistant, the prepared fiber has good chemical stability and is particularly suitable for sewage treatment.

[0043] The present invention will be described in detail below by way of examples. The amounts of materials used in the following examples are in parts by weight. The sources of the raw materials of each example are as follows:

[0044] Polyvinylpyrrolidone (PVP) was from Sinopharm Chemical Reagent Co., Ltd.;

[0045] Ethanol was from Sinopharm Chemical Reagent Co., Ltd.;

[0046] DMF was from Sinopharm Chemical Reagent Co., Ltd.;

[0047] Terephthalic acid was from Sinopharm Chemical Reagent Co., Ltd.;

[0048] 1,4-Naphthalenedicarboxylic acid was from Sinopharm Chemical Reagent Co., Ltd.;

[0049] 1,4-Cyclohexanedicarboxylic acid was from Sinopharm Chemical Reagent Co., Ltd.;

[0050] Zinc nitrate was from Aladdin Reagent Co., Ltd.;

[0051] Copper acetate was from Aladdin Reagent Co., Ltd.;

[0052] Cobalt chloride was from Aladdin Reagent Co., Ltd.;

[0053] Nickel nitrate was from Aladdin Reagent Co., Ltd.;

[0054] Ultra-high molecular weight polyethylene powder comes from Shanghai Lianle Chemical Technology Co., Ltd., with a weight-average molecular weight of 4.5 million g / mol;

[0055] Tris(4-nonylphenyl)phosphite was from Aladdin Reagent Co., Ltd.;

[0056] Vitamin E was from Aladdin Reagent Co., Ltd.;

[0057] β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester was from Aladdin Reagent Co., Ltd.;

[0058] Decalin was obtained from Jiangsu Zhongneng Chemical Technology Co., Ltd.

[0059] The strength and modulus of the obtained fiber were measured according to GB / T 14344-2008 standard;

[0060] The melting temperature is determined according to GB / T 19466.3-2004 standard;

[0061] The adsorption capacity was determined by the following method:

[0062] Weigh an ultra-high molecular weight polyethylene fiber with a mass of m, add a dye solution (methylene blue) with a volume of V and a concentration of c0, put it in a 30°C constant temperature water bath, and after adsorption for 10 hours, separate and absorb the supernatant. By measuring its ultraviolet absorption value and substituting it into the standard curve equation, the residual dye concentration c1 in the solution is calculated. The adsorption amount Q is calculated by the following formula:

[0063]

[0064] Preparation Example 1

[0065] Preparation of fillers

[0066] Dissolve 2.5 parts of polyvinylpyrrolidone (PVP, weight-average molecular weight of about 10,000 g / mol) in a mixed solution of 50 mL of ethanol and 50 mL of DMF, heat and stir at 120°C for 15 minutes, add 0.3 parts of zinc nitrate and 0.25 parts of terephthalic acid, continue to react at 120°C for 1 hour, centrifuge and wash to obtain a filler.

[0067] Preparation Example 2-5

[0068] The method of Preparation Example 1 was adopted, except that the amounts of reaction materials and dispersant were different. For details, see Material Table 1.

[0069] Table 1 Material components for preparing fillers

[0070]

[0071] Example 1

[0072] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 1, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0073] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0074] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0075] The prepared fiber has a strength of 35 cN / dtex, a modulus of 1562 cN / dtex, an adsorption capacity of 350 mg / g, and a melting temperature of 144°C.

[0076] Example 2

[0077] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 2 parts of filler prepared in Preparation Example 1, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse at 80° C. for 2 hours with 600W ultrasonic assisted stirring to form a spinning solution;

[0078] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0079] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0080] The prepared fiber has a strength of 33 cN / dtex, a modulus of 1587 cN / dtex, an adsorption capacity of 560 mg / g, and a melting temperature of 145°C.

[0081] Example 3

[0082] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 1, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0083] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 170°C, and the spinneret pressure is 3.2MPa;

[0084] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0085] The prepared fiber has a strength of 36 cN / dtex, a modulus of 1594 cN / dtex, an adsorption capacity of 350 mg / g, and a melting temperature of 144°C.

[0086] Example 4

[0087] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 1, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0088] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0089] Step 3: Stretch the primary filaments at a stretching ratio of 30 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0090] The prepared fiber has a strength of 28 cN / dtex, a modulus of 1348 cN / dtex, an adsorption capacity of 332 mg / g, and a melting temperature of 141°C.

[0091] Example 5

[0092] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 2, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0093] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0094] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0095] The prepared fiber has a strength of 35 cN / dtex, a modulus of 1560 cN / dtex, an adsorption capacity of 400 mg / g, and a melting temperature of 145°C.

[0096] Example 6

[0097] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0098] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0099] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0100] The prepared fiber has a strength of 35 cN / dtex, a modulus of 1550 cN / dtex, an adsorption capacity of 450 mg / g and a melting temperature of 145°C.

[0101] Example 7

[0102] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 4, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0103] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0104] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0105] The prepared fiber has a strength of 35 cN / dtex, a modulus of 1550 cN / dtex, an adsorption capacity of 200 mg / g, and a melting temperature of 142°C.

[0106] Example 8

[0107] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 5, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0108] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0109] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0110] The prepared fiber has a strength of 35 cN / dtex, a modulus of 1550 cN / dtex, an adsorption capacity of 300 mg / g, and a melting temperature of 142°C.

[0111] Example 9

[0112] Step 1: Add 150 parts of ultra-high molecular weight polyethylene powder, 1.5 parts of the filler of Preparation Example 2, 0.5 parts of tris(4-nonylphenyl)phosphite, and 0.5 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0113] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0114] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0115] The prepared fiber has a strength of 31 cN / dtex, a modulus of 1430 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 142°C.

[0116] Example 10

[0117] Step 1: Add 120 parts of ultra-high molecular weight polyethylene powder, 1.2 parts of the filler of Preparation Example 2, 0.5 parts of tris(4-nonylphenyl)phosphite, and 0.4 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0118] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0119] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0120] The prepared fiber has a strength of 32 cN / dtex, a modulus of 1400 cN / dtex, an adsorption capacity of 430 mg / g, and a melting temperature of 143°C.

[0121] Embodiment 11

[0122] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 0.5 parts of filler prepared in Preparation Example 2, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0123] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0124] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0125] The prepared fiber has a strength of 35 cN / dtex, a modulus of 1560 cN / dtex, an adsorption capacity of 200 mg / g, and a melting temperature of 144°C.

[0126] Example 12

[0127] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 3 parts of filler of Preparation Example 2, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 600W ultrasonic assisted stirring to form a spinning solution;

[0128] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0129] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0130] The prepared fiber has a strength of 35 cN / dtex, a modulus of 1570 cN / dtex, an adsorption capacity of 600 mg / g, and a melting temperature of 145°C.

[0131] Example 13

[0132] Step 1: add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 2, 0.1 parts of tris(4-nonylphenyl)phosphite, and 0.1 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl ester to 1500 parts of decalin, and stir and disperse them at 80° C. for 2 hours with 600W ultrasonic assistance to form a spinning solution;

[0133] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0134] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0135] The prepared fiber has a strength of 25 cN / dtex, a modulus of 1300 cN / dtex, an adsorption capacity of 400 mg / g, and a melting temperature of 140°C.

[0136] Embodiment 14

[0137] Step 1: add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 2, 0.5 parts of tris(4-nonylphenyl)phosphite, and 0.5 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl ester to 1500 parts of decalin, and stir and disperse them at 80° C. for 2 hours with 600W ultrasonic assisted stirring to form a spinning solution;

[0138] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0139] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0140] The prepared fiber has a strength of 38 cN / dtex, a modulus of 1580 cN / dtex, an adsorption capacity of 400 mg / g, and a melting temperature of 146°C.

[0141] Embodiment 15

[0142] Step 1: add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 2, 0.4 parts of tris(4-nonylphenyl)phosphite, and 0.4 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl ester to 1500 parts of decalin, and stir and disperse them at 80° C. for 2 hours with 600W ultrasonic assisted stirring to form a spinning solution;

[0143] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0144] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0145] The prepared fiber has a strength of 37 cN / dtex, a modulus of 1540 cN / dtex, an adsorption capacity of 400 mg / g, and a melting temperature of 145°C.

[0146] Example 16

[0147] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 2, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 4 hours at 300W ultrasonic assisted stirring at 50°C to form a spinning solution;

[0148] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0149] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0150] The prepared fiber has a strength of 34 cN / dtex, a modulus of 1450 cN / dtex, an adsorption capacity of 400 mg / g, and a melting temperature of 142°C.

[0151] Embodiment 17

[0152] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 2, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 1 hour at 100° C. with 1000W ultrasonic assisted stirring to form a spinning solution;

[0153] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0154] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0155] The prepared fiber has a strength of 33 cN / dtex, a modulus of 1500 cN / dtex, an adsorption capacity of 400 mg / g, and a melting temperature of 143°C.

[0156] Embodiment 18

[0157] Step 1: add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 3 hours at 70° C. with 500W ultrasonic assisted stirring to form a spinning solution;

[0158] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0159] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0160] The prepared fiber has a strength of 36 cN / dtex, a modulus of 1570 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 145°C.

[0161] Embodiment 19

[0162] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 800W ultrasonic assisted stirring at 90°C to form a spinning solution;

[0163] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0164] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0165] The prepared fiber has a strength of 37 cN / dtex, a modulus of 1580 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 145°C.

[0166] Embodiment 20

[0167] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 700W ultrasonic assisted stirring to form a spinning solution;

[0168] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 70°C, the homogenizing section temperature is 120°C, the conveying section temperature is 130°C, the twin-screw extruder pressure is 2.0MPa, the spinneret temperature is 150°C, and the spinneret pressure is 2.0MPa;

[0169] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0170] The prepared fiber has a strength of 32 cN / dtex, a modulus of 1450 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 142°C.

[0171] Embodiment 21

[0172] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 700W ultrasonic assisted stirring to form a spinning solution;

[0173] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 90°C, the homogenizing section temperature is 150°C, the conveying section temperature is 150°C, the twin-screw extruder pressure is 3.0MPa, the spinneret temperature is 160°C, and the spinneret pressure is 3.2MPa;

[0174] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0175] The prepared fiber has a strength of 36 cN / dtex, a modulus of 1550 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 146°C.

[0176] Embodiment 22

[0177] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 700W ultrasonic assisted stirring to form a spinning solution;

[0178] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 140°C, the homogenizing section temperature is 160°C, the conveying section temperature is 170°C, the twin-screw extruder pressure is 4.0MPa, the spinneret temperature is 170°C, and the spinneret pressure is 4.0MPa;

[0179] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0180] The prepared fiber has a strength of 37 cN / dtex, a modulus of 1560 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 146°C.

[0181] Embodiment 23

[0182] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 700W ultrasonic assisted stirring to form a spinning solution;

[0183] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 150°C, the homogenizing section temperature is 170°C, the conveying section temperature is 180°C, the twin-screw extruder pressure is 5.0MPa, the spinneret temperature is 180°C, and the spinneret pressure is 5.0MPa;

[0184] Step 3: Stretch the primary filaments at a stretching ratio of 35 times and a stretching temperature of 140° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0185] The prepared fiber has a strength of 34 cN / dtex, a modulus of 1500 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 143°C.

[0186] Embodiment 24

[0187] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 700W ultrasonic assisted stirring to form a spinning solution;

[0188] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0189] Step 3: Stretch the primary filaments at a stretching ratio of 25 times and a stretching temperature of 130° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0190] The prepared fiber has a strength of 28 cN / dtex, a modulus of 1350 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 141°C.

[0191] Embodiment 25

[0192] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 700W ultrasonic assisted stirring to form a spinning solution;

[0193] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0194] Step 3: Stretch the primary filaments at a stretching ratio of 30 times and a stretching temperature of 135° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0195] The prepared fiber has a strength of 36 cN / dtex, a modulus of 1550 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 145°C.

[0196] Embodiment 26

[0197] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 700W ultrasonic assisted stirring to form a spinning solution;

[0198] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0199] Step 3: Stretch the primary filaments at a stretching ratio of 40 times and a stretching temperature of 145° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0200] The prepared fiber has a strength of 40 cN / dtex, a modulus of 1600 cN / dtex, an adsorption capacity of 450 mg / g and a melting temperature of 145°C.

[0201] Embodiment 27

[0202] Step 1: Add 100 parts of ultra-high molecular weight polyethylene powder, 1 part of the filler of Preparation Example 3, 0.35 parts of tris(4-nonylphenyl)phosphite, and 0.35 parts of vitamin E to 1500 parts of decalin, and stir and disperse for 2 hours at 80° C. with 700W ultrasonic assisted stirring to form a spinning solution;

[0203] Step 2: adding the spinning solution to a twin-screw extruder, pumping it out through a metering pump and then extruding it through a spinneret to form primary filaments, wherein the feeding section temperature of the twin-screw extruder is 120°C, the homogenizing section temperature is 155°C, the conveying section temperature is 160°C, the twin-screw extruder pressure is 3.2MPa, the spinneret temperature is 165°C, and the spinneret pressure is 3.2MPa;

[0204] Step 3: Stretch the primary filaments at a stretching ratio of 50 times and a stretching temperature of 155° C. to obtain ultra-high molecular weight polyethylene fibers with adsorption effect.

[0205] The prepared fiber has a strength of 32 cN / dtex, a modulus of 1400 cN / dtex, an adsorption capacity of 450 mg / g, and a melting temperature of 142°C.

[0206] Embodiment 28

[0207] The method of Example 1 was followed, except that the spinneret temperature in step 2 was 145° C., and the draft ratio in step 3 was 20 times.

[0208] The strength of the prepared fiber is 22 cN / dtex, the modulus is 984 cN / dtex, the adsorption capacity is 325 mg / g, and the melting temperature is 138°C.

[0209] Comparative Example 1

[0210] The method of Example 1 was followed, except that no filler was added.

[0211] The strength of the prepared fiber is 35 cN / dtex, the modulus is 1487 cN / dtex, the adsorption capacity is 5 mg / g, and the melting temperature is 142°C.

[0212] Comparative Example 2

[0213] The method of Example 1 was followed, except that no antioxidant was added.

[0214] The strength of the prepared fiber is 21 cN / dtex, the modulus is 1087 cN / dtex, the adsorption capacity is 324 mg / g, and the melting temperature is 137°C.

[0215] Through the analysis of Examples 1, 2, 5, 6, 11, and 12, it can be seen that the selection of metal salts and polyacids in the filler has a great influence on the adsorption capacity of the filler and the prepared fiber. The adsorption capacity of the fillers prepared in Preparation Examples 2 and 3 is significantly better than that of the other preparation examples. The more fillers are added, the stronger the adsorption capacity of the obtained fibers is. Therefore, the adsorption capacity of the fibers prepared in Examples 5, 6, and 12 is greater.

[0216] By comparing Comparative Example 1 with Example 1, it can be seen that the filler contributes the most to the adsorption capacity of the prepared fiber; by comparing Comparative Example 2 with Example 2, it can be seen that the antioxidant can improve the strength, modulus and melting temperature of the prepared fiber; by comparing Example 28 with Example 1, it can be seen that a suitable stretching ratio is helpful to improve the strength, modulus and melting temperature of the fiber.

[0217] In general, the fiber prepared by the method provided by the present invention has strong adsorption capacity and good mechanical strength, and is particularly suitable for sewage treatment.

[0218] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An ultra-high molecular weight polyethylene fiber, characterized in that: The raw materials for preparing the ultra-high molecular weight polyethylene fiber include: ultra-high molecular weight polyethylene powder, antioxidant and filler; wherein the antioxidant accounts for 0.2-1wt% of the ultra-high molecular weight polyethylene powder, and the filler accounts for 0.5-3wt% of the ultra-high molecular weight polyethylene powder; wherein the filler is obtained by dissolving a metal salt and a polyacid organic ligand in a first solvent and reacting them.

2. The ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that: The antioxidant accounts for 0.6-0.8wt% of the ultra-high molecular weight polyethylene powder, and the filler accounts for 2-3wt% of the ultra-high molecular weight polyethylene.

3. The ultra-high molecular weight polyethylene fiber according to claim 1 or 2, characterized in that: The ultra-high molecular weight polyethylene fiber has an adsorption capacity of 200-600 mg / g, a strength of 25-40 cN / dtex, a modulus of 1300-1600 cN / dtex, and a melting temperature of 140-150°C.

4. The ultra-high molecular weight polyethylene fiber according to any one of claims 1 to 3, characterized in that: The metal salt is selected from at least one of zinc salt, copper salt, cobalt salt and nickel salt; Preferably, the zinc salt is selected from at least one of zinc nitrate, zinc acetate, and zinc chloride; the copper salt is selected from at least one of copper nitrate, copper acetate, and copper chloride; the cobalt salt is selected from at least one of cobalt nitrate, cobalt acetate, and cobalt chloride; and the nickel salt is selected from at least one of nickel nitrate, nickel acetate, and nickel chloride. Preferably, the polyacid organic ligand is selected from at least one of terephthalic acid, 1,4-naphthalene dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, 2,2'-biphenyl dicarboxylic acid, 2,5-dihydroxy terephthalic acid, and 3,3',5,5'-biphenyl tetracarboxylic acid.

5. The ultra-high molecular weight polyethylene fiber according to claim 4, characterized in that: The metal salt is 0.1-0.5 parts by weight, and the polyacid organic ligand is 0.05-0.3 parts by weight; Preferably, the metal salt is 0.2-0.4 parts by weight, and the polyacid organic ligand is 0.1-0.2 parts by weight.

6. A method for preparing ultra-high molecular weight polyethylene fiber, characterized in that: The ultra-high molecular weight polyethylene fiber is obtained by spinning a spinning solution containing a second solvent, ultra-high molecular weight polyethylene powder, an antioxidant and a filler; wherein the filler is obtained by dissolving a metal salt and a polyacid organic ligand in a first solvent and reacting them.

7. The preparation method according to claim 6, characterized in that: The ultra-high molecular weight polyethylene powder accounts for 5-10 wt% of the second solvent; Preferably, the antioxidant accounts for 0.2-1 wt% of the ultra-high molecular weight polyethylene powder, and the filler accounts for 0.5-3 wt% of the ultra-high molecular weight polyethylene powder.

8. The preparation method according to claim 6 or 7, characterized in that: The process of forming the spinning solution includes: dispersing the ultra-high molecular weight polyethylene powder, antioxidant, and filler in the second solvent to form the spinning solution; Preferably, the dispersion process comprises: stirring with ultrasound assistance at 50-100° C. for 1-4 h; Preferably, the mixture is stirred at 70-90°C for 2-3 hours with ultrasonic assistance.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The spinning process includes: stretching, wherein the stretching ratio is 25-50 times, preferably 30-40 times.

10. Use of the ultra-high molecular weight polyethylene fiber according to any one of claims 1 to 5 or the ultra-high molecular weight polyethylene fiber obtained by the preparation method according to any one of claims 6 to 9 in sewage treatment.

Citation Information

Patent Citations

  • Dye absorption agent and preparation method and application thereof

    CN106390919A

  • Adsorption material and preparation method and application thereof

    CN108339525A

  • Preparation method for chitosan nanofiber membrane of in-situ growth of metal-organic frameworks

    CN108816064A

  • Fiber-based adsorption material and preparation method thereof and application of fiber-based adsorption material in palladium recovery

    CN113171762A